Preparation of pH-sensitivity hydrogel microspheres and potassium diformate sustained-release and antibacterial performance analysis - GUO Xiao-wei; LI Yu-yan; WANG Xiu-li; YANG Zhong-xin; CHEN Nan-chun; XIE Qing-lin (Cailiao gongcheng, 2021)
Potassium diformate (KDF) is a novel substitute for antibiotics, which is not widely used in livestock production. The P-type molecular sieve (Zeolite P) was prepared by hydrothermal method with loading KDF and dispersed in the carboxymethyl cellulose (CMC) solution. The dispersed CMC mixed solution was added dropwise to the FeCl3 solution for cross-linking. Chitosan-carboxymethyl cellulose-Zeolite P-potassium diformate pH-sensitive hydrogel antibacterial microspheres were prepared by coacervation method. FT-IR, TGA and SEM results show that CS and CMC form the structurally stable polyelectrolyte complex through ionic bonds, and Zeolite P is included in the CMC matrix. The difference in swelling study indicates that the hydrogel microspheres have high pH-sensitivity and can be applied for sustained-release under different pH value. The slow-release kinetics study shows that antimicrobial microspheres have a certain sustained-release effect on KDF. The first-order kinetic model and the Higuchi model fits well with release data. In vitro antibacterial experiments, the antibacterial microspheres display significant antibacterial property against Escherichia coli and Staphylococcus aureus in the concentration of the antibacterial solution at 24 mg/mL and 48 mg/mL. Antibacterial microspheres can effectively inhibit the growth of bacteria, and the antimicrobial microsphere model provides a theoretical basis for the use of KDF.